2019
DOI: 10.5152/tud.2019.48457
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical, oncological, and functional outcomes of robot-assisted and laparoscopic radical prostatectomy in patients with prostate cancer

Abstract: printing of pelvic fracture urethral injuries-fusion of technology and urethroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The higher the stage and PSA value, the greater the probability of PSMs [ 19 ]. The PSM rate of robot-assisted laparoscopic radical prostatectomy reported in the literature ranges from 10.5 to 45.9% [ 3 , 20 ]. In this study, the PSM rates in the Xi group and Si group were as high as 53.7 and 60.2%, respectively, but there was no significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the stage and PSA value, the greater the probability of PSMs [ 19 ]. The PSM rate of robot-assisted laparoscopic radical prostatectomy reported in the literature ranges from 10.5 to 45.9% [ 3 , 20 ]. In this study, the PSM rates in the Xi group and Si group were as high as 53.7 and 60.2%, respectively, but there was no significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 3 articles were found in the literature that summarized early patient outcomes after SP RARC [5][6][7] . Including our institution, a total of 21 patients were included in the final analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports indicated that patients with RALP had shorter surgical times, less estimated blood loss, and shorter lengths of hospital stay than those who underwent LRP [7][8][9] . Our results were in accord with those from other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Robot-assisted radical prostatectomy (RALP) has been widely used, and its use is increasing [4][5][6] . Several reports have indicated that RALP is associated with a shorter surgical time, less estimated blood loss, and shorter length of hospital stay than pure-laparoscopic radical prostatectomy (LRP) [7][8][9] .…”
Section: Main Text Introductionmentioning
confidence: 99%